Biocontrol-based strategies for improving soil health and managing plant-parasitic nematodes in coffee production - Saikai, Kanan K.; Oduori, Celestine; Situma, Evans; Njoroge, Simon; Murunde, Ruth; Kimenju, John W.; Miano, Douglas W.; Haukeland, Solveig; Coyne, Danny (Frontiers in Plant Science, 2023)
Coffee is an important commodity for Kenya, where production is steadily declining, despite a global rise in demand. Of the various constraints affecting production, plant parasitic nematodes are a significant, but often overlooked, threat. As a perennial crop, treating plantations once infected with nematodes becomes difficult. The current study evaluated the drenching application of two biocontrol agents, Trichoderma asperellum and Purpureocillium lilacinum, for their nematode control efficacy, as well as their impact on the soil nematode community structure on mature, established coffee trees in Kenya. Seven Arabica coffee field trials were conducted over two years on trees of various ages. All the fields were heavily infested with Meloidogyne hapla, the first report of the species on coffee in Kenya. Both fungal biocontrol agents were detected endophytically infecting roots and recovered from soil but not until six months after initial applications. The population densities of M. hapla had significantly declined in roots of treated trees 12 months after the initial application, although soil nematode density data were similar across treatments. Based upon the maturity index and the Shannon index, treatment with T. asperellum led to improved soil health conditions and enrichment of diversity in the microbial community. Application of P. lilacinum, in particular, led to an increased abundance of fungivorous nematodes, especially Aphelenchus spp., for which P. lilacinum would appear to be a preferred food source. The soils in the trials were all stressed and denuded, however, which likely delayed the impact of such treatments or detection of any differences between treatments using indices, such as the functional metabolic footprint, over the period of study. A longer period of study would therefore likely provide a better indication of treatment benefits. The current study positively demonstrates, however, the potential for using biologically based options for the environmentally and climate-smart management of nematode threats in a sustainable manner on established, mature coffee plantations.